Comparative outcomes of ceftazidime-avibactam versus meropenem-vaborbactam for KPC-producing Enterobacterales infections - Sara M. Karaba; Dariusz A. Hareza; MUNITA SEPULVEDA, JOSE MANUEL; MARTINEZ SOLIS, JOSE RODRIGO WALDEMAR; Yehudit Bergman; Armani M. Hawes; Zackery P. Bulman; Sara E. Cosgrove; Patricia J. Simner; Pranita D. Tamma (American Society for Microbiology, 2026)
ABSTRACT Thirty-day mortality was similar in a propensity-score-weighted cohort of 73 patients with KPC-producing Enterobacterales infections treated with ceftazidime-avibactam or meropenem-vaborbactam. Emergence of resistance was higher in the ceftazidime-avibactam group (12% vs 0%); putative resistance mechanisms included porin mutations ( Klebsiella pneumoniae ) and R2 loop structural changes in AmpC ( Enterobacter cloacae complex).